"A woman CEO? You'd better think twice!": Exploring career challenges of women CEOs at multinational corporations in South Korea. Issue 1 (11th February 2019) - Cho, Yonjoo; Park, Jiwon; Han, Soo Jeoung; Ho, Yedam
Abstract : Purpose: The purpose of this paper is to explore how multinational corporations' (MNCs') women leaders in South Korea (Korea) have overcome career challenges in the process of becoming CEOs. The two guiding questions for this study included: what career challenges have MNCs' women leaders in Korea faced to become CEOs? How have they overcome their career challenges? Design/methodology/approach: The authors used a basic qualitative research design, the goal of which is to understand how people make sense of their lives and experiences. Qualitative data were collected by semi-structured interviews with 15 women CEOs at MNCs in Korea to capture their lived experiences (challenges and strategies) in their careers. The authors used NVivo 11, a qualitative data analysis software, to analyze the interview data. Findings: From data analysis, the authors identified five themes including: becoming a CEO, key success factors, MNC culture, career challenges and career development strategies. The authors found that in the process of becoming CEOs, 15 women leaders faced career challenges that are largely generated by traditional culture, work stress and work–life balance. The authors also found that the women leaders became CEOs through diverse on-the-job experiences (e.g. marketing and sales) and positions (e.g. managers, senior managers and regional directors) with organizational support (e.g. supervisor support). Research limitations/implications: Given research on organizational support for leadership, human resource practices and working conditions, this study's findings have qualitatively confirmed the importance of organizational support for women CEOs' career success. For theory building in women in leadership, the authors suggest that researchers investigate the complex process of becoming women CEOs, including their early experiences in their career in tandem with family background, organizational climate and national culture. Practical implications: The study findings on women CEOs' career strategies can be used as a reference for women in the leadership pipeline who aspire to take leadership positions in organizations. A lack of role models or mentors for women leaders is one of the reasons why women give up on their career. Learning career strategies (e.g. global development programs, mentoring and networks) that women CEOs have employed to overcome their career challenges can help women in the leadership pipeline from their early career on. Originality/value: The authors found that both internal and external factors combined were instrumental in the women CEOs' career success. What stood out from this study was that the women's desirable personality attributes might not have materialized without the MNC culture that has been supportive for these women. The women CEOs shared their company's values and philosophy that is based on gender equality, received supervisor support that is crucial for their career success, experienced diverse jobs and positions along the way and were recognized for their work ethic. Given research on women leaders conducted largely in western contexts, this qualitative study on the lived experiences of women CEOs in MNCs contributes to emerging non-western research by capturing the importance of culture that is uniquely Korean.